PERAN OFFICE OF THE UNITED NATIONS HIGH COMMISSIONER FOR HUMAN RIGHTS (OHCHR) DALAM MENANGGULANGI PERMASALAHAN HAK ASASI MANUSIA DI MALI - Aris Perdana; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is an study into international political which aims specifically to discusses the role of the Office of the United Nations High Commissioner for Human Rights (OHCHR), in dealing with ethnic conflicts between the Dogon and Fulani tribes in Mali country. Ethnic conflict is relevant to international relations insofar as it impacts human rights, security, and the economies of the in volved. Based on a number of cases, ethnic tensions ethnic trigger more conflicts than religious or cultural problems. Because ethnicity is very sensitive and often used as a tool to achieve political or economic interests.This research uses the perspective of pluralism and international organizational theory to attempt to understand the role of the OHCHR in solving human rights issues in Mali. The level of analysis in this study uses a group behaviour approach to analyze how the activities of individuals or organizations involved in international relations. This basic framework is needed to help the define appropriate goals and direc analysis.In this study, the author want  to describe the actions taken by OHCHR to help resolve the human rights issues in the Dogon and Fulani ethnic conflicts in Mali in accordance with their role as international organizations.